Unlacing carnal margins : portraits by Angela Stewart - Stewart, Angela (Curtin University, 2010)
In this research I examine artistic doubt as a way to unlace the becoming of a portrait. My interest is in the personal encounter between the painter and sitter. My muse is the sixteenth-century Italian portrait painter, Sofonisba Anguissola and through both creative practice and exegetical writing, which takes an epistolary approach, I investigate the process, mistakes and interruptions of making that can impact on portrait painting. As such doubt is positioned as caches of ontological moments.